The relationship between safety culture maturity and mental health among workers in automotive industry - Abdul Ghapa, Nur Adiba; Hashim, Hasni; Rasdi, Irniza; Zainal Abidin, Emilia (Universiti Putra Malaysia, 2023)
Introduction: The present study aims to investigate the relationship between the level of safety culture maturity, socio-demographic characteristics and occupational information with mental health among automotive workers. Methods: This cross-sectional study was conducted among automotive workers. A Safety Culture Assessment Tools (SASTO) questionnaire was used to measure the safety culture maturity level while Depression Anxiety Stress Scale (DASS)-21 was used to measure the level of depression, anxiety, and stress. Convenience sampling method was used to distribute the questionnaires to 18 automotive industry companies in Malaysia. There were 224 completed questionnaires. Result: Result showed that on average the companies have moderate level of safety culture which indicates calculative level. More than half of the respondents reported to have mild to extremely level of severe depression, anxiety, and stress. Small percentage of respondents having severe to extremely severe depression (9.9%), anxiety (18.7%) and stress (1.8%). None of the socio-demographic and occupation information parameters were found to be statistically significantly associated with depression and stress. There were significant association between age, position at work, and working experience and anxiety. Working experience has the strongest association with anxiety. The safety culture has no relationship with depression, anxiety, and stress. Conclusion: The level of depression, anxiety and stress were high among respondents, therefore it is important to create a balance job demands and occupational skills to improve the workers mental health. Also, improvement strategies are needed to improve safety culture to a higher level.